La mort à l’haïtienne et la parole rituelle Hadriana dans tous mes rêves de René Depestre - Żurawska, Anna (Romanica Silesiana)
The aim of the article is to explore the role of selected rituals in the novel Hadriana dans tous mes rêves by René Depestre. The narration is focused on the zombification of the eponymous character on her wedding day and the sudden disappearance of her tomb after the funeral ceremony. Both rituals not only illustrate the social system of Haiti, but also reflect the particular relation between the narrator living in exile (like the author of the book) and his native island personified by Hadriana. First, the novel is analyzed from the anthropological perspective; then, the metaphorical dimension of the rituals described in the book is stressed. Finally, the ritual, possessing some degree of inherent agency, is presented as a symbolic act of performative utterance. Key words: ritual, voodoo and Christian anthropology, marvelous realism (réalisme merveilleux), performative utterance